The supply services of the British army in the South African War, 1899-1902 - Page, A (1976)
The purpose of this study is to analyse the methods and results of the supply services of the British army in the South African war. The study will consider both the preparations made for the war and the changes made after it and covers administration both in the War Office and with the army in the field. It tries to show how the complex task of moving the army and providing it with transport, arms, stores, food and animals needed to keep it effective was performed, and to what extent the material provided met the needs of the army both in quality and in quantity. Continued in thesis ... .